2012
DOI: 10.1051/0004-6361/201118035
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct halo populations in the solar neighborhood

Abstract: Context. In Papers I and II of this series, we have found clear indications of the existence of two distinct populations of stars in the solar neighborhood belonging to the metal-rich end of the halo metallicity distribution function. Based on high-resolution, high S/N spectra, it is possible to distinguish between "high-alpha" and "low-alpha" components using the Results. The "high-alpha" halo stars have ages 2-3 Gyr larger than the "low-alpha" ones, with some probability that the thick-disk stars have ages i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
176
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(211 citation statements)
references
References 98 publications
31
176
4
Order By: Relevance
“…This confirms the notion that the Galactic halo was formed and assembled very early on as suggested by both theory (Robertson et al 2005;Font et al 2006;Zolotov et al 2009Zolotov et al , 2010Font et al 2011) and observations (e.g. Schuster et al 2012). The theoretical work of Robertson et al (2005) and Font et al (2006) lays out what Schuster et al (2012) refer to as a 'dualaccretion' scenario.…”
Section: Implications For the Formation Of The Galactic Halosupporting
confidence: 83%
See 4 more Smart Citations
“…This confirms the notion that the Galactic halo was formed and assembled very early on as suggested by both theory (Robertson et al 2005;Font et al 2006;Zolotov et al 2009Zolotov et al , 2010Font et al 2011) and observations (e.g. Schuster et al 2012). The theoretical work of Robertson et al (2005) and Font et al (2006) lays out what Schuster et al (2012) refer to as a 'dualaccretion' scenario.…”
Section: Implications For the Formation Of The Galactic Halosupporting
confidence: 83%
“…Yet, the recent simulations of Font et al (2011) found that in situ stars can be as much as 3-4 Gyr younger than the accreted population. Schuster et al (2012) argued that their α-rich and α-poor populations can be explained by a scenario where an initial disk/bulge formed in a monolithic collapse producing the α-rich population. At later times, the α-rich stars in the primeval disk were scattered into the halo via merging events that subsequently populated the α-poor component of the halo.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations